Developing a YouTube-Based Digital Storytelling Video to Support Students’ Understanding of Narrative Text - Bethanya Br Sipahutar; Sarah Ramadani; Anggraini Thesisia Saragih; Khairul Azmi Siagian (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2026)
This study aims to develop a storytelling-based learning media in the form of a YouTube video to support students’ understanding of narrative text based on their learning needs. This study employed a Research and Development (R&D) design using the ADDIE model, focusing on the stages of analysis and development. The data were collected through a questionnaire as part of the needs analysis to identify students’ responses toward listening and repetition activities, as well as the difficulties they face in understanding narrative texts. The results show that students generally respond positively to listening and repetition. However, they still experience difficulties in understanding the storyline and vocabulary. The findings also indicate that students need learning support in the form of audio, visual elements, and vocabulary assistance. Based on these findings, a learning product was developed in the form of a YouTube-based digital storytelling video entitled “Learn Narrative Text Through Fun Storytelling (Listen, Repeat & Retell)”. The video integrates storytelling, repetition, vocabulary explanation, and speaking practice to support students’ comprehension. Due to time limitations, this study was limited to the development of a prototype and has not yet included expert validation. Therefore, future research is recommended to conduct validation to evaluate the feasibility and effectiveness of the developed product.